2013
DOI: 10.1016/j.neuron.2013.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Making Waves: Initiation and Propagation of Corticothalamic Ca2+ Waves In Vivo

Abstract: Corticothalamic slow oscillations of neuronal activity determine internal brain states. At least in the cortex, the electrical activity is associated with large neuronal Ca(2+) transients. Here we implemented an optogenetic approach to explore causal features of the generation of slow oscillation-associated Ca(2+) waves in the in vivo mouse brain. We demonstrate that brief optogenetic stimulation (3-20 ms) of a local group of layer 5 cortical neurons is sufficient for the induction of global brain Ca(2+) waves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
225
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 239 publications
(258 citation statements)
references
References 52 publications
28
225
5
Order By: Relevance
“…2A, Fig. S3A, and Movie S2) (16,(21)(22)(23)(24)(25)(26). We found that such global brain activity (GBA) identified in CaS was mostly followed by brainwide activity in simultaneously recorded HemoS with a delay of a few seconds (Fig.…”
Section: Spontaneous Waves Of Cas Frequently Propagated Across the Wholementioning
confidence: 79%
See 3 more Smart Citations
“…2A, Fig. S3A, and Movie S2) (16,(21)(22)(23)(24)(25)(26). We found that such global brain activity (GBA) identified in CaS was mostly followed by brainwide activity in simultaneously recorded HemoS with a delay of a few seconds (Fig.…”
Section: Spontaneous Waves Of Cas Frequently Propagated Across the Wholementioning
confidence: 79%
“…To date, optical imaging and electrophysiological studies in animals have reported multiple heterogeneous dynamics of large-scale spontaneous neuronal activity (16,(21)(22)(23)(24)(25)(26)(27)(28). Waves of activity that propagate across the cortical network are commonly observed across different experimental setups (16,(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Specific features of the method are that it records strictly from the local clusters of cells that were labeled with the Ca 2+ indicator dye and that the recorded neuronal signals result exclusively from action potential activity, but not from subthreshold depolarization. The Ca 2+ signal detected by each fiber is collected from a local domain with a diameter of about 300-400 μm (9,10,24). The specific size of the domain depends on the dimensions of the cortical region that was stained with the Ca 2+ indicator, but also on the intensity of the excitation light and the collection efficiency of emitted fluorescence by the optical fiber.…”
Section: Discussionmentioning
confidence: 99%